Impact of fenofibrate on choroidal neovascularization formation and VEGF-C plus VEGFR-3 in Brown Norway rats. (September 2018) - Zhao, Jian-Feng; Hua, Hai-Rong; Chen, Qian-Bo; Guan, Meng; Yang, Jin-Hui; Xi, Xiao-Ting; Li, Yan; Geng, Yu
Abstract: Objective: This study aims to explore the possible role of fenofibrate in inhibiting choroidal neovascularization (CNV) in Brown Norway (BN) rats. Methods: BN rats underwent binocular retinal laser photocoagulation to induce CNV. On day one, fenofibrate was injected into the vitreous cavity of rats in the control and experimental groups. Fundus fluorescein angiography (FFA), isolectin B4-FITC staining, immunofluorescence staining, qRT-PCR and western blot were performed at 1, 2, 3 and 4 weeks to observe the morphological changes of CNV and the expression of the vascular endothelial growth factor C (VEGF-C) and the vascular endothelial growth factor receptor-3 (VEGFR-3). Results: CNV with the spontaneous gradual regression and scarring phenomenon appeared in BN rats. In neovascularization, VEGF-C was mainly distributed in the ganglion cell layer, while VEGFR-3 was mainly expressed in the choroid. In the control group, choroidal VEGF-C initially increased, and subsequently decreased, while VEGFR-3 level maintained a constant level after the decrease. Both had a decreasing expression in the retina. The early formation of CNV was significantly weakened in the experimental group, but there was no difference in the later period. VEGF-C and VEGFR-3 expression in the choroid and retina were lower than in the control group. Furthermore, VEGFR-3 protein was not expressed in the retina. However, this gradually increased in the early period and declined in the terminal stage in the choroid. Conclusion: VEGF-C and VEGFR-3 participated in the laser-induced CNV formation in BN rats. Fenofibrate could inhibit CNV formation. Highlights: VEGF-C and VEGFR-3 participated in the laser-induced CNV formation in BN rats. VEGFR-3 may play the role of bi-directional regulation of CNV. Fenofibrate could inhibit CNV formation.